Leishmaniasis as a Manifestation of Immune Reconstitution Inflammatory Syndrome (IRIS) in HIV-Infected Patients: A Literature Review. (September 2015) - Badaró, Roberto; Gonçalves, Larissa O.; Gois, Luana L.; Maia, Zuinara Pereira Gusmão; Benson, Constance; Grassi, Maria Fernanda Rios
Introduction: After the onset of highly active antiretroviral therapy (HAART), some HIV-infected patients present a severe inflammation in response to a latent or a previously treated opportunistic pathogen termed immune reconstitution inflammatory syndrome (IRIS). Few reports of tegumentary and visceral leishmaniasis have been described in association with IRIS. Methods: A systematic literature review of IRIS in association with leishmaniasis identified 34 reported cases. Results and Discussion: The majority of these occurred in males 4 months following the onset of HAART. The mean CD4 count before HAART was 94 ± 77 cells/mm 3, increasing to 5 times the initial value between the onset of HAART and IRIS presentation. Visceral leishmaniasis and post–kala-azar dermal leishmaniasis were the most commonly reported clinical manifestations, followed by tegumentary leishmaniasis and uveitis. Conclusions: Commonly found characteristics included cutaneous involvement, regardless of Leishmania species; appearance of lesions unrelated to time of probable Leishmania infection; rapid recovery of CD4 count following HAART; and rapid progression.